2001
DOI: 10.1021/ma011419s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Self-Assembly of Conjugated Polymer Precursors Containing Dichlorocarbonate Groups by Living Ring-Opening Metathesis Polymerization

Abstract: We have used the living ring-opening metathesis polymerization reaction with Cl2(PCy3)2RuCHPh to generate a new class of conjugated polymer precursors containing the reactive group 1,2-dichlorocarbonate in their backbone. These polymers possess narrow molecular weight distributions and are easily processable. We have incorporated the 1,2-dichlorocarbonate monomers into block copolymers and have shown that these systems can self-assemble in selective solvents to generate spherical micellar aggregates (TEM). Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It has been shown that defined amphiphilic block copolymers can be obtained by ROMP. Several aspects were investigated, such as the formation of stable micelles and nanoparticles, the use as drug delivering material, , as polymers with special electrooptical and electroactive properties and for the preparation of inorganic nanoparticles. For most of the above-mentioned applications, the self-assembly at the nanoscale has to be very precise and homogeneous. This can only be achieved by a very well controlled synthesis of the block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that defined amphiphilic block copolymers can be obtained by ROMP. Several aspects were investigated, such as the formation of stable micelles and nanoparticles, the use as drug delivering material, , as polymers with special electrooptical and electroactive properties and for the preparation of inorganic nanoparticles. For most of the above-mentioned applications, the self-assembly at the nanoscale has to be very precise and homogeneous. This can only be achieved by a very well controlled synthesis of the block copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…We are currently investigating the properties of the ROMP polymers of 4 in further detail and generating these from enantiomerically pure monomers. In addition, we are studying possible methods for the conversion of the polymer backbone in 5 to a conjugated form, in analogy with our previous studies on a similar system, 11 to create Ru(II)-containing conjugated polymers in a controlled manner.…”
Section: Discussionmentioning
confidence: 99%
“…Because of their unique photophysical and redox properties, these molecules have been extensively investigated as components of light-harvesting assemblies and photochemically driven molecular devices, as well as photocatalysts and biological probes. For these applications, binuclear and multinuclear assemblies containing Ru(II) diimine complexes are typically constructed in stepwise syntheses, which can be time-consuming. On the other hand, the ROMP reaction of Ru(II) polypyridyl-containing monomers could result in more straightforward generation of multichromophoric polymers and block copolymers in a living fashion, with controlled molecular weights and narrow molecular weight distributions. , A number of polymeric systems containing Ru(II) diimines have been generated . Free-radical polymerization 12a-d and, more recently, anionic polymerization 12e-i have been used to synthesize precursors that were converted to Ru(bpy) 3 2+ -containing homopolymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16) [139]; (7) norbornenes connected to pincer-ligated phenylpalladium(II) derivatives (e.g. 17) [140,141]; (8) norbornenes fused to the N-hydroxysuccinimide ring system [142]; (9) norbornenes and oxanorbornenes of general structure 18 [143]; (10) norbornenecarboxylate esters of complex fluorinated benzyl alcohol derivatives [144]; (11) polyethylene glycol-bound norbornenes [145]; (12) adenine-containing norbornene derivatives [146]; (13) norbornene derivatives featuring a thymidine ring associated with a 1,6-diamidopyridine derivative (19) [147]; (14) bicyclo[3.2.0]hept-6-ene [148]; (15) norbornene-fused succinimides [149]; (16) norbornenes attached to oligothiophene units (e.g. 20) [150]; (17) 3,5-siloxane-bridged cyclopentenes (e.g.…”
Section: Polymerization Reactionsmentioning
confidence: 99%